Oxidative Stability of Cooked Chicken Breast Burgers Obtained from Organic, Free-range and Conventionally Reared Animals - Lawlor, J.B.; Sheehan, E.M.; Delahunty, C.M.; Morrissey, P.A.; Kerry, J.P. (International Journal of Poultry Science, 2003)
The oxidative stability of cooked chicken breast burgers from chickens reared on organic (n=3), free-range (n=3), and conventional (n=3) diets was determined. α-Tocopherol and fatty acid concentrations were also determined. Organic, free-range and conventional chicken breasts were obtained from local retail outlets. Significant (Pconventional. It was concluded that cooked breast burgers from broilers fed organic diets had a lower shelf-life (oxidative) stability compared with cooked breast burgers from broilers free-range and conventional diets. Stability, in the present work, appeared to be related more to α-tocopherol concentration than to fatty acids.